Strontium doped Lead Zirconate Titanate ceramics: Study of calcination and sintering process to improve piezo effect - Khalid, Muhammad; Shoaib, Muhammad; Khan, Amir Azam (American Scientific Publisher, 2011)
Perovskite crystal structure is found in many ionic solids like CaTiO3, BaTiO3 and Lead Zirconate Titanates (PZT). In this structure off-center position of cations in oxygen octahedral causes polarization and produces direct and indirect piezoelectric responses in ceramic materials that are suitable for many ultrasonic applications. In the present study 9% Sr doped PZT ceramics were prepared and their dielectric and piezoelectric properties measured. X ray Diffraction (XRD) analysis of calcined powders demonstrated a decrease in the PbO content during the calcination stage at 850 C. This was counterbalanced by adding excess PbO at the time of preparation of mixtures. Sintering was carried out at 1200 C for 2 hours in lead rich atmosphere. The properties achieved were Dielectric Constant (K)=1440, Tangent Loss (Tan =00062, Charge Coefficient (d33=335 pC/N and density = 755 g/cm3. SEM analysis of sintered samples demonstrated that grain size was 2–3 m with clean grain boundaries and no large size porosity observed. XRD analysis of sintered pellets exhibited that material prepared was free of any precipitated phase usually harmful for the piezo effect.